Heavy metals contamination in paddy soil and water and associated dermal health risk among farmers - Rudzi, Siti Khairunnisaq; Ho, Yu Bin; Abd Kharni, Intan Idayu (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: This study aims to quantify the concentrations of Cu, Cr, Zn, Ni, Pb, As and Cd in paddy soil and water and assess their potential dermal health risk to the farmers at Kampung Sawah Sempadan, Malaysia. Methods: 72 water samples and 72 soil samples were collected and analysed using inductively coupled plasma mass spectrometry (ICP-MS). 117 respondents were interviewed using a questionnaire to obtain the exposure information for dermal health risk assessments. Results: All elements in water did not exceed the recommended concentration by Malaysia National Water Quality Standard (NWQS) and Food and Agriculture Organization (FAO). Nevertheless, the maximum concentration of As (31.49 mg/kg) in paddy soil exceeded the Dutch Target Value for soil protection (29 mg/kg). There was no significant chronic non-carcinogenic health risk for farmers working in the paddy soil and water (HQ<1, HI<1). The carcinogenic health risk of As was in the acceptable risk level (10-6 to 10-4). Conclusion: The contamination of the selected heavy metals in the paddy soil and water at Kampung Sawah Sempadan were lower than the available standards except for As in soil which exceeds the recommended value by Dutch target value. The health risk to these heavy metals were also minimal and within the acceptable level.